Application of Seismic Geomorphology and Spectral Decomposition: A Case of Field B in PM318 Block, Malay Basin - Abdul Hakim, Siti Amanina Farhanah (IRC, 2016)
In this study, the seismic geomorphology and spectral decomposition methods are used together to evaluate Field B which is located within the PM318 block in the NNE part of the Malay Basin for stratigraphic traps potential. Seismic geomorphology is the study of the ancient geomorphic patterns of the earth to gain insights on the paleo-environments by exploiting 3D seismic data. 3D seismic data is very useful as it allows geoscientists to image preferred geomorphological structures along picked horizons or time slices. In this study, fluvial seismic geomorphology within Field B or specifically the channel systems are thoroughly evaluated in order to upgrade its stratigraphic trap potential as most of the previous wells in the area have been drilled on structural traps. Within the PM318 block, there are many fields discovered and wells penetrated but most are left plugged and abandoned as they are considered as marginal fields due to the small amount of volume or reserve found which is due to the gentle structure of most of the anticlines along with the very small vertical closure that traps the hydrocarbons. Therefore, focus will be given on finding stratigraphic trap, especially channels within the area of study using the seismic geomorphology methods to enhance its visualization and the channel systems delineated are then assessed for their hydrocarbon potential using the spectral decomposition method.